13.4k views
3 votes
Match each trinomial to its factored form. (y - 2)(3y + 4) 3y2 + 2y - 8 (y + 2)(3y - 4) 3y2 + 13y - 10 (3y + 2)(y - 5) 3y2 - 13y - 10 (3y - 2)(y + 5) 3y2 - 2y - 8 arrowBoth arrowBoth arrowBoth arrowBoth

2 Answers

3 votes

Answer:


3y^2 + 2y - 8=(3y-4)(y+2)


3y^2 + 13y - 10=(3y-2)(y+5)


3y^2 - 13y - 10=(3y+2)(y-5)


3y^2 - 2y - 8=(3y+4)(y-2)

Explanation:

Given trinomial are


3y^2 + 2y - 8\\3y^2 + 13y - 10\\3y^2 - 13y - 10\\3y^2 - 2y - 8.

we have to convert these in factored form


3y^2 + 2y - 8=3y^2+6y-4y-8

=
3y(y+2)-4(y+2)

=
(3y-4)(y+2)


3y^2 + 13y - 10=3y^2+15y-2y-10

=
3y(y+5)-2(y+5)

=
(3y-2)(y+5)


3y^2 - 13y - 10=3y^2-15y+2y-10

=
3y(y-5)+2(y-5)

=
(3y+2)(y-5)


3y^2 - 2y - 8=3y^2-6y+4y-8

=
3y(y-2)+4(y-2)

=
(3y+4)(y-2)




User Danyhow
by
6.0k points
2 votes

Answer:

Match each trinomial to its factored form:

1.
(y-2)(3y+4)

Multiplying each term in the first expression by each term in a second expression.


y(3y+4) -2(3y+4)

Using distributive property:
a\cdot (b+c) = a\cdot b+ a\cdot c


(3y^2 + 4y) -(6y + 8)

Remove the parenthesis, we have;


3y^2 + 4y -6y -8

combine like term ;


3y^2-2y -8

2.
(y+2)(3y-4)

Multiplying each term in the first expression by each term in a second expression.


y(3y-4) +2(3y-4)

Using distributive property:
a\cdot (b+c) = a\cdot b+ a\cdot c


(3y^2 - 4y) + (6y - 8)

Remove the parenthesis, we have;


3y^2 - 4y + 6y - 8

combine like term ;


3y^2 + 2y -8

3.
(3y+2)(y-5)

Multiplying each term in the first expression by each term in a second expression.


3y(y-5) +2(y-5)

Using distributive property:
a\cdot (b+c) = a\cdot b+ a\cdot c


(3y^2 - 15y) + (2y - 10)

Remove the parenthesis, we have;


3y^2 - 15y + 2y - 10

combine like term ;


3y^2 -13y -10

4.
(3y-2)(y+5)

Multiplying each term in the first expression by each term in a second expression.


3y(y+5) -2(y+5)

Using distributive property:
a\cdot (b+c) = a\cdot b+ a\cdot c


(3y^2 + 15y) - (2y + 10)

Remove the parenthesis, we have;


3y^2+ 15y - 2y - 10

combine like term ;


3y^2 + 13y -10

Column 1 Column 2


(y-2)(3y+4)
3y^2-2y -8


(y+2)(3y-4)
3y^2+ 2y -8


(3y+2)(y-5)
3y^2 -13y -10


(3y-2)(y+5)
3y^2 + 13y -10